Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Konsumen Dalam Keputusan Pembelian Produk Holtikultura di Kebun Praktek Universitas Nusa Nipa - Asterliana Subu; Yoseph Yakob Da Rato; Sarlina Noni (Peneliti.net, 2023)
Purchasing decisions are consumers' understanding of the wants and needs of a product by assessing from existing sources by setting purchase goals and identifying alternatives so that decision makers to buy are accompanied by behavior after making a purchase. Purchasing decisions are heavily influenced by cultural, social, personal, and psychological characteristics. The research was conducted in an agricultural paraktek garden from August 15 – December 17, 2022. Le but de l’étude: découvrir les facteurs qui influencent le comportement des consommateurs dans les décisions d’achat de produits horticoles dans le jardin de la Faculté de technologie alimentaire, d’agriculture et de pêche de l’Université Nusa Nipa Maumere. Based on the results of the study, there are 3 factors that influence consumer behavior in purchasing decisions, namely psychological factors, personality factors and social factors. The largest respondent response value for psychological factors on each statement was 89.82% . with indicators: feeling satisfied after buying organic vegetables (98.3%).